ANALISIS SISTEM INFORMASI AKUNTANSI PERSEDIAAN BAHAN BAKU DALAM KELANCARAN PROSES PRODUKSI DI MASA PANDEMI : Study.Kasus Usaha Mikro Omah Teh Nganjuk - Ni’matul Ijadiyah; Iman Supriadi (LPPM Universitas Bina Bangsa, 2022)
Accounting information system or (AIS) is a system designed to collect and display accounting information so that accountants and company executives can make appropriate decisions and have the aim of processing evidence of recording and reporting all information related to all financial transactions, documents or accounting records. There are several important functions in a working group on accounting information systems, including: storing and collecting data about work activities. Not only that, the information system can also be used to process and transact data into information that can be used to properly control and process decisions related to assets in the organizational system. Omah Teh Nganjuk business which is located on Jl. WR Supratman No.6, Mangundikaran, Mangun Dikaran, Kec. Nganjuk, Nganjuk Regency is the object that we choose in this research. Omah Teh Nganjuk is a family business brand engaged in packaged food and ready-to-drink beverages. Nganjuk tea is an herbal tea made from black tea, green tea, roselle flowers and jasmine flowers which are mixed and combined to make fresh drinks and are useful for health. This study aims to provide information about the accounting information system for raw materials inventory in the Omah Teh Nganjuk business. This research uses qualitative research methods, for data analysis techniques using descriptive analysis with a qualitative approach. Data collection techniques in conducting this research are interviews and observations. Based on the results of the analysis, the implementation of the accounting system for Omah Teh Nganjuk's raw material inventory is very good. The method of determining the cost or inventory cost can also be applied to the company, by choosing the first-in, first-out method. In the smooth production contained in the raw material inventory system in the Omah Teh Nganjuk business, more emphasis is placed on physical inventory counting in order to be able to make fictitious records on the warehouse book, with the separation of functions it can also speed up the production process